Effect of in vitro Anti-diabetic Activity of Cassia siamea Flowers and Leaves Extract - Damsud, Thanakorn; Penprapai, Pensri; Rongsawat, Premjit (The Journal of Chulabhorn Royal Academy, 2020)
Background: Diabetes is a chronic metabolic disease usually caused by defects in insulin secretion. In addition, diabetes is a potential risk of developing the initiation of its complications, as a result of prolonged high blood glucose level. Objective: The aim of this work was to reduce blood glucose level potential of flowers and leaves extract from Cassia siamea through dipeptidyl peptidase IV (DPP-IV) inhibitor, -glucosidase inhibitory activity, glucose adsorption and glucose diffusion in vitro. Methods: The methanol crude extracts of flowers and leaves extract from C. siamea were evaluated for DPP-IV inhibitor, -glucosidase inhibitory activity from rat intestinal (matase and sucrase), glucose adsorption, glucose diffusion in vitro and preliminary of phytochemical screening. Results: Preliminary, phytochemical screening showed the presence of flavonoids, alkaloids, and phenolic compounds in flowers and leaves extract. In this study, the methanol extract of leaves showed stronger DPP-IV inhibitor and -glucosidase inhibitory activity (maltase and sucrase) with the IC50 values of 0.40, 3.77 and 3.64 mg/mL, respectively than flowers extract. Vildaglipin and acarbose, based on standard reference for DPP-IV and -glucosidase (maltase and sucrase) inhibitory activity, has IC50 values of 0.32, 0.36 and 0.97 mg/mL, respectively. In addition, the methanol extract of flowers and leaves showed most potent glucose adsorption and glucose diffusion retardation. Conclusion: Thus, the results from the studied methanol extracts flowers and leaves could be developed as the anti-hyperglycemic remedy for diabetes therapy.